دور السياسة النقدية في تدنية فجوة الناتج مع إشارة إلى تجربة الولايات المتحدة الأمريكية (المجلة العراقية للعلوم الاقتصادية, 2018)
Most schools agree on the economic impact of inflationary monetary policy in the long term, as proved many historical facts the risk of excessive money supply growth and its negative impact on the national economy and its imopse too many of the economic crisis.As for monetary policy, as it has an inflationary impact, so it, also has a developmental impact to stimulate the local output in the short term, on the one hand, and the accumulation of that effect over a certain time scale, it could lead to the expansion of the capacity of the economy, energy (potential output) on the other.So this study tend to follow-up the developmental impact of monetary policy, but in the long term, to prove the validity of the assumption of there is a development impact of monetary policy in the long term or not, as the monetary policy in the short term determine the average direction of monetary policy in the long term.Therefore, if a country follows an expansive monetary policy on an annual basis, in a period of ten years, the direction of monetary policy has to affect on each of the actual output and potential output at a certain extent. So, this study highlights the developmental impact of monetary policy on the output gap, which implies the developmental impact of monetary policy on economy in long-term, and its application to the U.S. economy, which is characterized by an active and diverse economy, and exposed, at the same time, many of the economic crises.